Respuesta :

Step-by-step explanation:

M=NPQ

m/pq=Npq/pq

pq is going to cancel, you left with N

N= m/pq

To solve for q, we have to make q the subject.

m = Npq

divide both sides of the equation by NP

M/NP= q

that's the answer

Answer:

N = M/(PQ)

Q = M/(NP)

Step-by-step explanation:

Given that

M = NPQ

  • then if we divide by PQ at both sides of the equation

        M/(PQ) = NPQ/(PQ)

        M/(PQ) = N

  • On the other hand, if we divide by NP at both sides of the equation

        M/(NP) = NPQ/(NP)

        M/(NP) = Q

ACCESS MORE